ESTONIAN PUBLISHING SECTOR AT THE TURN OF THE 20TH AND 21ST CENTURIES: EMERGENCE OF E-BOOK MARKET - MÖLDRE, AILE (Knygotyra, 2014)
The article includes an overview of the development of e-publishing in Estonia. The treatment is based on the analysis and comparison of existing research, mainly student papers; statistical data from the database of Statistics Estonia and the National Library of Estonia, articles in the periodical press and homepages of various institutions. The beginning of the article presents the description of the publishing industry during the 2000s. In accordance with the development of economy the book production has moved from the peak in the mid-2000s to recession in 2008–2010. The declining market led to the decrease in print runs (since 2008) and book title production (since 2010). The number of publishers, however, increased even during the crisis. The small-language market is of no interest to international companies, so the book industry works on local capital. Estonia is characterised by early adoption and wide use of the Internet. The web publishing by organisations, associations and individuals is widespread since mid 1990s, but commercial publishers remained aside of this trend. As in many other European countries, especially small countries, the publishers were uncertain about the application of copyright in the digital environment and technological skill gaps. These worries were largerly overcome by the establishment of e-publishing service providers in 2010, which led to the take off in the publishing of e-books. The number of e-books produced and the sales have increased a number of times, but their share of the book market is rather marginal. The book buyers and readers still hold to traditional book form. The official cultural policy, however, favours e-books and supports different projects that provide free access to Estonian classical literature and modern authors. KEYWORDS: e-publishing, e-book, publishing industry, book title production, e-book market, Estonia.